Impact of Agricultural Loan Disbursement and Chemical Fertilizer Use on the Rice Production in Bangladesh (Bangladesh Journal of Public Administration, 2020)
Agriculture is one of the important issues of Bangladesh, where a larger share is related to it for livelihood, food, and socio-economic activities. Agriculture draws considerable attention and is the backbone of the Bangladesh economy. Besides enhancing food and raw materials, agriculture also enhances employment opportunities to a vast number of the population. Agriculture is affected by many factors; among those two crucial factors are agricultural credit and chemical fertilizer. This paper examined the effect of agricultural loan & chemical fertilizer on the total rice production in Bangladesh during the time 1995 to 2016. The study has used data from the economic review 2017. Data are found stationary at the difference at 1% and 5% level of significance using Augment Dicky Fuller (ADF) test. Then the study adopted multiple regressions to see the influence on agricultural loan and chemical fertilizer on total rice production. The result showed that agricultural credit has a positive & statistically significant effect on total rice production, and chemical fertilizer has a positive effect on the total rice production of Bangladesh but not statistically significant. Keyword(s): Total rice production, agricultural loan, chemical fertilizer, multiple regression. J.E.L. Classification: Q10, Q14, O13, C19.